2020
DOI: 10.1029/2019gl086821
|View full text |Cite
|
Sign up to set email alerts
|

Aurora Basin, the Weak Underbelly of East Antarctica

Abstract: The East Antarctic Ice Sheet (EAIS) has the potential to raise global sea levels by ∼52 m.Here, we model the evolution of select EAIS catchments to 2100 using three basal melt rate parameterizations and force our model with surface mass balance and ocean thermal anomalies from 10 global climate models. While the domain loses mass under low-emission scenarios, it gains ∼10-mm sea-level rise equivalent ice volume (SLRe) under high-emission scenarios. The primary region of thinning is within 50 km upstream of Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…In the latter experiments, water is diverted west toward the region of outflow and does not induce melting directly at the grounding line (Figure S8). These rumples have been cited as a pinning point of TG in both observational and modeling studies Pelle et al, 2020;Roberts et al, 2018); however, the findings presented here suggest that these topographic highs serve the dual-purpose of acting as both a pinning point and barrier to warm water inflow.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the latter experiments, water is diverted west toward the region of outflow and does not induce melting directly at the grounding line (Figure S8). These rumples have been cited as a pinning point of TG in both observational and modeling studies Pelle et al, 2020;Roberts et al, 2018); however, the findings presented here suggest that these topographic highs serve the dual-purpose of acting as both a pinning point and barrier to warm water inflow.…”
Section: Discussionmentioning
confidence: 61%
“…Recent modeling studies have found that changes in sub-shelf ocean conditions are the primary driver of the observed dynamic changes TG has been experiencing over the past two decades (Gwyther et al, 2018;Pelle et al, 2020;Roberts et al, 2018). These studies, however, do not capture the full impact of changing sub-shelf ocean conditions on the system due to their use of simplified parameterizations of sub-ice shelf basal melt and/or fixed ice sheet geometry.…”
mentioning
confidence: 99%
“…As the weak underbelly of East Antarctica, Wilkes Land has been losing mass at accelerated rates due to warm water intrusion (Rignot et al, 2019;Pelle et al, 2020). This paper is the first comprehensive investigation of both short-term and long-term GL changes on Totten and Moscow University Glaciers.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of rapid glacier retreat and ice mass loss from key outlet basins in Antarctica constitutes the greatest uncertainty in estimates of future sea level rise (IPCC, 2021). The Aurora Subglacial Basin (ASB), East Antarctica, has significant potential to contribute to sea level rise (Pelle et al., 2020), containing approximately 7 m of sea‐level equivalent ice (Morlighem et al., 2020), of which 3.5 m is grounded below sea level (Greenbaum et al., 2015). The ASB has dominated recent ice mass loss from East Antarctica, losing 20 ± 14 Gt year −1 of ice between 2003 and 2019 (Smith et al., 2020).…”
Section: Introductionmentioning
confidence: 99%